The diversity of wild orchids in the southern slope of Mount Merapi, Yogyakarta, Indonesia eight years after the 2010 eruption - Febri Yuda Kurniawan; Fauzana Putri; Ahmad Suyoko; Himawan Masyhuri; Maya Purqi Sulistianingrum; Endang Semiarti (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Kurniawan FY, Putri F, Suyoko A, Masyhuri H, Sulistianingrum MP, Semiarti E. 2020. The diversity of wild orchids in the southern slope of Mount Merapi, Yogyakarta, Indonesia eight years after the 2010 eruption. Biodiversitas 21: 4457-4465. The ecosystem of the slopes of Mount Merapi is mountain tropical forest which is frequently affected by volcanic activities. The dynamics of the volcano affect the diversity and abundance of orchids in the ecosystem. Tritis is an area included in the Turgo Hill of the southern slope of Mount Merapi and is under the management of Mount Merapi National Park. The ecosystem in Tritis area classified as lower mountain forest and it has been affected by Mount Merapi eruption. This study aimed to do an inventory of orchid species in Tritis to know the diversity and abundance of orchids that exist in this area. In particular, we were interested to investigate the diversity after the 2010 eruption. The sampling was done using plot method by establishing four observation plots with size of each plot was 500 m x 20 m. The orchids found were identified using literature and we calculated the density, frequency, relative density, relative frequency and important value index. This study found 24 species of orchids, consisting of 15 species of epiphytic orchids, 6 terrestrial species, 2 holomycotropic species and 1 semiterrestrial species. There were 6 species of orchids with the highest density and 2 species with the highest frequency value. Thrixspermum sp. and Mycaranthes oblitterata were the most dominant species in Tritis based on important value index. Overall, the diversity of orchids in Tritis can be categorized as high, likely because Tritis environment supports the growth of epiphytic orchids, but it is less favorable for the growth of terrestrial, holomycotropic and semiterrestrial orchids. The results of this study can serve as baseline information to monitor the dynamics of orchid diversity and abundance in relation to the highly volcanic activities of Mount Merapi.